Attitudes Toward Psychological Test Use in Indonesia - Christiany Suwartono; Justinus Budi Santoso (ANIMA Indonesian Psychological Journal, 2016)
Psychological tests in Indonesia have been evolving very slowly. Most psychological practice is still using outdated versions of tests. Psychometric properties such as validity, reliability, and even norms are often based on outdated data or entirely omitted in the manual. Thus, the ability of the tests to yield valid data for various purposes is highly questionable. Most test users, including the psychological community, seem to be indifferent to this situation as they keep using these tests despite the risk of error in the test results which could have legal implications. In this study, we did a survey about test users’ attitudes towards psychological tests. We recruited 149 participants, of which 71.8% were female. The age ranged from 22 to 71 years old (M = 29.4; SD = 7.32). The survey assessed participants’ opinion toward legal properties of psychological test on a five-point scale. All participants had an undergraduate or higher degree in Psychology. The results were interesting. Participants acknowledge that they should use reputable test even though they perceived the price is too expensive. Also, they are willing to pay if those tests are up to date and provide adequate psychometric properties. The results indicate that there is a big opportunity for psychologists and psychometricians to gather forces to fulfill these needs and make more con-tribution to the society.